A Technology-based Intervention to Increase Reading Comprehension of Morphosyntax Structures. (9th August 2019) - Cannon, Joanna E; Hubley, Anita M; O'Loughlin, Julia I; Phelan, Lauren; Norman, Nancy; Finley, Alayna
Abstract: The purpose of this study was to examine the effectiveness of a technology-based intervention (LanguageLinks: Syntax Assessment and Intervention®; Laureate Learning Systems, Inc., 2013 ) to improve reading comprehension for d/Deaf and hard of hearing (DHH) elementary students. The intervention was a self-paced, interactive program designed to scaffold learning of morphosyntax structures. Participants included 37 DHH students with moderate to profound hearing levels, 7–12 years of age, in Grades 2–6. Assessment data were collected pre- and post- an 8-week intervention using a randomized control trial methodology. Findings indicate the intervention did not appear to be effective in improving performance, and 17 out of 36 morphosyntax structures were found difficult to comprehend for participants in the treatment group. These difficult structures included aspects of pronominalization, the verbal system, and number in nouns. Results are compared to previous research, with recommendations for future areas of research related to increasing knowledge of morphosyntax for learners who are DHH.